Research note: Effect of load reductions over consecutive sets on repetition performance - Willardson, J. M.; Kattenbraker, M. S.; Khairallah, M.; Fontana, F. E. (The Journal of Strength and Conditioning Research, 2010)
When performing consecutive sets of a resistance exercise, maintaining performance within a specified repetition range has been shown to be essential for achieving muscular adaptations conducive to different training goals. However, maintaining repetition performance can be difficult when using shorter rest intervals between sets (i.e., =1 min), which may require load reductions. Therefore, the purpose of the current study was to compare repetition performance when keeping the load constant or reducing the load by different percentages during a lower-body workout. Ten repetition maximum (10RM) loads were established for the back squat, leg curl, and leg extension exercises. Subjects performed 4 workouts under the following load conditions: (a) constant load for all sets, (b) 5% load reduction after each set, (c) 10% load reduction after each set, and (d) 15% load reduction after each set. Pairwise comparisons indicated that, when averaged across sets, significantly fewer repetitions were accomplished for the back squat and leg curl within the constant condition vs. the 15% condition (p < 0.05). Conversely, for the leg extension, there were no significant differences in the repetitions accomplished between conditions (p > 0.05). Pairwise comparisons also indicated that, when averaged across exercises, significantly fewer repetitions were accomplished for set 3 within the constant, 5%, and 10% conditions vs. the 15% condition (p < 0.05). In summary, the back squat and leg curl required 15% load reductions per set to maintain repetition performance. Conversely, load reductions were not necessary for the leg extension.